Positive electrode active material, method of preparing positive electrode active material, and rechargeable lithium battery including positive electrode having positive electrode active material
Patent Information
- Application Number
- CN202610528276.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-24
- Filing Date
- 2026-04-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0026]根据一些实施方式的制备正电极活性物质的方法可在使制造成本最小化的同时提供表现出长循环寿命特性的正电极活性物质。
Smart Images

Figure CN122992014A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to a positive electrode active material, a positive electrode having the positive electrode active material, and a rechargeable lithium battery including a positive electrode having the positive electrode active material. Background Technology
[0002] Portable information devices (such as cellular phones, laptops, or smartphones) already use rechargeable lithium batteries with high energy density and portability as their power source. Recently, there has been active research into using high-energy-density rechargeable lithium batteries as a power source or energy storage source for hybrid or electric vehicles.
[0003] To develop rechargeable lithium batteries suitable for the aforementioned applications, various positive electrode active materials are being researched. For example, lithium nickel-based oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides, or lithium cobalt-based oxides are primarily used as positive electrode active materials.
[0004] Recently, with the rapid increase in demand for rechargeable lithium batteries with superior performance, such as superior capacity or superior energy density, there is a need to develop rechargeable lithium batteries that can exhibit long cycle life characteristics. Summary of the Invention
[0005] Some embodiments provide a positive electrode active material capable of exhibiting long cycle life characteristics, a positive electrode having the positive electrode active material, and a rechargeable lithium battery including a positive electrode having the positive electrode active material.
[0006] According to some embodiments of this disclosure, the positive electrode active material may include a first positive electrode active material and a second positive electrode active material. The first positive electrode active material may include particles having a lithium cobalt-based oxide. The particles of the first positive electrode active material may have an average particle size D of about 9 μm to about 25 μm. 50 The second positive electrode active material may include particles having a lithium cobalt-based oxide and a layered carbon coating layer on the surface of the particles of the second positive electrode active material. The particles of the second positive electrode active material may have an average particle size D of about 1 μm to about 9 μm. 50 .
[0007] In some embodiments, based on 100% by weight of the second positive electrode active material, the second positive electrode active material may include a carbon coating layer in an amount from about 0.05% by weight to about 5.0% by weight.
[0008] In some embodiments, the carbon coating layer of the second positive electrode active material may include graphene having a layered structure comprising 2 to 50 layers.
[0009] In some implementations, the graphene in the carbon coating may be derived from (or derived from) plate-like carbon materials.
[0010] In some embodiments, the carbon material may include graphene, graphite, or a combination thereof.
[0011] In some embodiments, the average size D of the carbon material 50 It can be less than or equal to about 2.5 μm.
[0012] In some embodiments, the average size D of the carbon material 50 It can be approximately 50 nm to approximately 900 nm.
[0013] In some embodiments, the thickness of the carbon material may be less than or equal to about 1.0 μm.
[0014] In some embodiments, the carbon coating may be in the form of a continuous film or islands.
[0015] In some embodiments, the carbon coating may have a strength of 0.15 to 0.50 as indicated by a Raman spectrum at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I represents D / I G .
[0016] In some embodiments, the first positive electrode active material may include less than or equal to about 0.01% by weight of carbon material on the surface of each particle of the first positive electrode active material.
[0017] In some embodiments, the lithium cobalt-based oxide of the first positive electrode active material and the lithium cobalt-based oxide of the second positive electrode active material may be the same as or different from each other, and may each be independently represented by the following: Li a1 Co x1 M 1 y1 O 2- b1 X b1 Furthermore, 0.9 ≤ a1 ≤ 1.8, 0.7 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.3, 0.9 ≤ x1 + y1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1. M 1 X can be one or more of the elements Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr. X can be one or more of the elements F, P, and S.
[0018] In some embodiments, the lithium cobalt-based oxide of the first positive electrode active material and the lithium cobalt-based oxide of the second positive electrode active material each further contain aluminum. The amount of aluminum in the second positive electrode active material based on 100% by weight of the total metals other than lithium in the second positive electrode active material may be greater than the amount of aluminum in the first positive electrode active material based on 100% by weight of the total metals other than lithium in the first positive electrode active material.
[0019] In some embodiments, based on a total of 100% by weight of the first positive electrode active material and the second positive electrode active material, the positive electrode active material may include the first positive electrode active material in an amount from about 20% by weight to about 95% by weight. Based on a total of 100% by weight of the first positive electrode active material and the second positive electrode active material, the positive electrode active material may include the second positive electrode active material in an amount from about 5% by weight to about 80% by weight.
[0020] A method for preparing a positive electrode active material according to some embodiments of this disclosure may include: preparing a first positive electrode active material comprising particles containing lithium cobalt-based oxide, the particles of the first positive electrode active material having an average particle size D of about 9 μm to about 25 μm. 50 The second positive electrode active material is prepared by dry mixing (dry mixing) particles of the second positive electrode active material with plate-shaped carbon material. The particles of the second positive electrode active material may include lithium cobalt-based oxide and may have an average particle size D of about 1 μm to about 9 μm. 50 ; and a mixture of the first positive electrode active material and the second positive electrode active material.
[0021] In some embodiments, the method may further include preparing a carbon material such that the carbon material has an average size D less than or equal to about 2.5 μm. 50 .
[0022] In some embodiments, the preparation of the second positive electrode active material may include mixing the particles of the second positive electrode active material and the carbon material using a mixer, such as a Nobilta mixer, at a speed of about 1,000 s. -1 approximately 9,000s -1 The shear rate and the blade rotation speed of less than or equal to about 20 m / s are used to mix the particles and carbon materials of the second positive electrode active material.
[0023] In some embodiments, preparing the second positive electrode active material may include mixing particles of the second positive electrode active material with an amount of carbon material ranging from about 0.05% by weight to about 5.0% by weight, based on a total of 100% by weight of particles of the second positive electrode active material and carbon material.
[0024] A rechargeable lithium battery according to some embodiments of this disclosure may include a positive electrode, a negative electrode, and an electrolyte. The positive electrode may include a current collector and a layer of positive electrode active material on the current collector. The layer of positive electrode active material may include the positive electrode active material as described above.
[0025] The positive electrode active material according to some embodiments can minimize degradation due to charging and discharging and improve particle strength. Furthermore, the positive electrode according to some embodiments can improve adhesion strength and conductivity to the electrode plate, and the rechargeable lithium battery according to some embodiments can exhibit excellent cycle life characteristics and also have high capacity and high energy density.
[0026] The method for preparing positive electrode active materials according to some embodiments can provide positive electrode active materials exhibiting long cycle life characteristics while minimizing manufacturing costs. Attached Figure Description
[0027] Figures 1 to 4 A diagram illustrating a rechargeable lithium battery according to some embodiments of the present disclosure.
[0028] Figure 5 Scanning electron microscope images showing the surface of the second positive electrode active material according to some embodiments of the present disclosure.
[0029] Figure 6 Transmission electron microscope images showing a cross-section of a second positive electrode active material according to some embodiments of the present disclosure. Detailed Implementation
[0030] Specific implementations will be described in detail below so that those skilled in the art can readily implement them. However, implementations of this disclosure may take many different forms and are not to be construed as limited to those described herein.
[0031] The terminology used herein is for descriptive purposes only and is not intended to limit the scope of this disclosure. Unless the context clearly specifies otherwise, singular expressions include plural expressions.
[0032] "Combination" refers to mixtures, laminates, complexes, copolymers, alloys, blends, and reaction products of the constituent elements.
[0033] In this document, it should be understood that terms such as “comprising,” “including,” or “having” are intended to indicate the presence of the features, quantities, steps, elements, or combinations thereof embodied, but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.
[0034] In the accompanying drawings, for clarity, the thickness of layers, films, panels, and / or regions is exaggerated, and the same reference numerals denote the same elements throughout the specification. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it may be directly on said other element, or there may be intermediate elements present. In contrast, when an element is referred to as being "directly on" another element, there are no intermediate elements.
[0035] In this article, “layer” includes not only the geometry formed on the entire surface when viewed from a plan view, but also the geometry formed on a portion of the surface.
[0036] The average particle size can be measured using methods well known to those skilled in the art, such as by a particle size analyzer or by transmission electron microscopy or scanning electron microscopy images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering, performing data analysis, counting the number of particles in each particle size range, and calculating from the obtained value and / or measurement results. Unless otherwise defined, the average particle size can mean the diameter D of the particles having a cumulative volume of 50% of the particle size distribution. 50 As used herein, unless otherwise defined, the average particle size means the diameter D of the particles representing 50% of the cumulative volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of approximately 20 particles in a scanning electron microscope image. 50 .
[0037] In this article, "or" is not interpreted as having an exclusive meaning; for example, "A or B" will be interpreted as including A, B, and A+B.
[0038] The term "metal" is interpreted as encompassing common metals, transition metals, and metalloids (semi-metals).
[0039] Positive electrode active material
[0040] According to some embodiments, the positive electrode active material may include: a first positive electrode active material, the first positive electrode active material comprising a lithium cobalt-based oxide and having an average particle size D of about 9 μm to about 25 μm. 50 The first positive electrode active material comprises particles containing lithium cobalt-based oxide and a layered carbon coating on the surface of the particles, and has an average particle size D of about 1 μm to about 9 μm. 50 The first positive electrode active material with a relatively large average particle size can be represented as large particles, and the second positive electrode active material with a relatively small average particle size can be represented as small particles.
[0041] Typically, for positive electrode active materials including lithium cobalt-based oxides, designs have been proposed to maximize capacity and energy density by mixing large particles with relatively large average particle sizes and small particles with relatively small average particle sizes. However, a problem exists: particle degradation progresses relatively rapidly, reducing battery cycle life.
[0042] According to some embodiments, the positive electrode active material may simultaneously comprise both large and small particles to maximize capacity and energy density. Meanwhile, because only the small particles have a carbon coating on their surface, the degradation of the small particles can be minimized, and the cycle life characteristics of the rechargeable lithium battery can be improved.
[0043] Furthermore, the second positive electrode active material includes a layered carbon coating on its surface. Since even a small amount of carbon material can coat the surface of the active material particles, adhesion strength and conductivity are increased. Therefore, even with the use of small amounts of binder and conductive material during the manufacture of the positive electrode, high adhesion strength and conductivity with the electrode plate can be achieved. Additionally, by reducing the amount of binder and conductive material used in the manufacture of the positive electrode, the amount of positive electrode active material can be increased, enabling the rechargeable lithium battery including the positive electrode active material to exhibit high capacity and high energy density characteristics.
[0044] First positive electrode active material
[0045] The first positive electrode active material may include particles comprising lithium cobalt-based oxides and may have an average particle size D of about 9 μm to about 25 μm. 50 .
[0046] The lithium cobalt-based oxide of the first positive electrode active material can be represented by chemical formula 1:
[0047] [Chemical Formula 1]
[0048] Li a1 Co x1 M 1 y1 O 2-b1 X b1 .
[0049] In chemical formula 1, 0.9 ≤ a1 ≤ 1.8, 0.7 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.3, 0.9 ≤ x1 + y1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1; M 1 X is one or more of the elements Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr; and X is one or more of the elements F, P, and S.
[0050] The lithium cobalt-based oxide of the first positive electrode active material may further include aluminum. The lithium cobalt-based oxide of the first positive electrode active material can be represented by chemical formula 2:
[0051] [Chemical Formula 2]
[0052] Li a2 Co x2 Al y2 M 2 z2 O 2-b2 X b2 .
[0053] In chemical formula 2, 0.9 ≤ a² ≤ 1.8, 0.881 ≤ x² ≤ 0.987, 0.013 ≤ y² ≤ 0.019, 0 ≤ z² ≤ 0.1, 0.9 ≤ x² + y² + z² ≤ 1.1, and 0 ≤ b² ≤ 0.1; M 2 X is one or more of the elements B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr; and X is one or more of the elements F, P, and S.
[0054] In chemical formula 2, 0.883 ≤ x² ≤ 0.987, 0.013 ≤ y² ≤ 0.017, 0 ≤ z² ≤ 0.1, or 0.883 ≤ x² ≤ 0.985, 0.015 ≤ y² ≤ 0.017, 0 ≤ z² ≤ 0.1. Furthermore, in chemical formula 2, 0.9 ≤ a² ≤ 1.5, 0.9 ≤ a² ≤ 1.2, or 0.98 ≤ a² ≤ 1.0.
[0055] In the lithium-cobalt-based oxide of the first positive electrode active material, based on 100% by weight of total metals excluding lithium, the amount of Al can be less than or equal to about 0.9% by weight (less than or equal to about 9,000 ppm), for example less than or equal to about 0.88% by weight, less than or equal to about 0.86% by weight, less than or equal to about 0.84% by weight, less than or equal to about 0.82% by weight, or less than or equal to about 0.8% by weight and may be greater than or equal to about 0.6% by weight, greater than or equal to about 0.62% by weight, greater than or equal to about 0.64% by weight, greater than or equal to about 0.66% by weight, greater than or equal to about 0.68% by weight, or greater than or equal to about 0.7% by weight. When the amount of Al meets the above range, the positive electrode active material is structurally stable at high voltages, and its capacity, resistance, and / or cycle life characteristics can be improved.
[0056] The average particle size D of the first positive electrode active material 50The particle size can be from about 9 μm to about 25 μm, and can be, for example, from about 10 μm to about 25 μm, from about 11 μm to about 23 μm, or from about 12 μm to about 20 μm. When the average particle size D of the first positive electrode active material... 50 When the above range is met, the structural stability of the positive electrode active material can be improved, and a long cycle life characteristic of the rechargeable lithium battery including the positive electrode active material can be achieved. The average particle size D of the first positive electrode active material... 50 The particle size distribution can be obtained by randomly selecting about 20 particles from a scanning electron microscope image of the particles, measuring their particle size (diameter, major axis, or major axis length), and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0057] The first positive electrode active material may include less than or equal to about 0.01% by weight, for example, from about 0% by weight to about 0.01% by weight, less than or equal to about 0.009% by weight, less than or equal to about 0.008% by weight, less than or equal to about 0.007% by weight, less than or equal to about 0.006% by weight, or less than or equal to about 0.005% by weight of carbon material on the surface of the particles. Because the first positive electrode active material may not include carbon material on the surface of the particles, there is no lower limit to the amount of carbon material.
[0058] Based on a total of 100% by weight of the first positive electrode active material and the second positive electrode active material, the first positive electrode active material may be included in an amount of about 20% to about 95% by weight, for example, about 30% to about 90% by weight, about 45% to about 85% by weight, or about 60% to about 80% by weight. When the amount of the first positive electrode active material meets the above range, the capacity and mixing density of the positive electrode can be improved, and the cycle life characteristics and energy density of the rechargeable lithium battery can be improved.
[0059] Second positive electrode active material
[0060] The second positive electrode active material may include particles containing lithium cobalt-based oxides and a layered carbon coating on the surface of the particles, and may have an average particle size D of about 1 μm to about 9 μm. 50 .
[0061] The average particle size D of the active material of the second positive electrode 50 The particle size can be from about 1 μm to about 9 μm, for example, from about 1.5 μm to about 8.8 μm, from about 2 μm to about 8.5 μm, or from about 2.5 μm to about 8.3 μm. When the average particle size D of the second positive electrode active material... 50When the above range is met, the structural stability of the positive electrode active material can be improved, and a long cycle life characteristic of the rechargeable lithium battery including the positive electrode active material can be achieved. The average particle size D of the second positive electrode active material... 50 The particle size distribution can be obtained by randomly selecting about 20 particles from a scanning electron microscope image of the particles, measuring their particle size (diameter, major axis, or major axis length), and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0062] The lithium cobalt-based oxide of the first positive electrode active material and the lithium cobalt-based oxide of the second positive electrode active material may be the same as or different from each other, and may be represented independently by the above chemical formula 1.
[0063] The lithium cobalt-based oxide of the second positive electrode active material may further include aluminum. If both the lithium cobalt-based oxide of the first and second positive electrode active materials further contain aluminum, the amount of aluminum based on 100% by weight of the total metals other than lithium in the second positive electrode active material can be greater than the amount of aluminum based on 100% by weight of the total metals other than lithium in the first positive electrode active material. Because the amount of aluminum in relatively rapidly deteriorating small particles increases, structural stability at high voltages can be ensured, and at the same time, the capacity, resistance, or cycle life characteristics of the rechargeable lithium battery including the positive electrode active material can be improved.
[0064] The lithium cobalt-based oxide of the second positive electrode active material can be represented by chemical formula 3:
[0065] [Chemical Formula 3]
[0066] Li a3 Co x3 Al y3 M 3 z3 O 2-b3 .
[0067] In chemical formula 3, 0.9 ≤ a³ ≤ 1.8, 0.878 ≤ x³ ≤ 0.985, 0.015 ≤ y³ ≤ 0.022, 0 ≤ z³ ≤ 0.1, 0.9 ≤ x³ + y³ + z³ ≤ 1.1, and 0 ≤ b³ ≤ 0.1, and M 3 It is one or more of the elements B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr.
[0068] In chemical formula 3, 0.881≤x3≤0.984, 0.016≤y3≤0.019, 0≤z3≤0.1; or 0.9≤a3≤1.5, 0.9≤a3≤1.2, or 0.98≤a3≤1.0.
[0069] In the lithium cobalt-based oxide of the second positive electrode active material, based on 100% by weight of total metal excluding lithium, the amount of Al can be less than or equal to about 1.0% by weight, for example less than or equal to about 0.98% by weight, less than or equal to about 0.96% by weight, less than or equal to about 0.94% by weight, less than or equal to about 0.92% by weight, or less than or equal to about 0.90% by weight, and can be greater than or equal to about 0.70% by weight, greater than or equal to about 0.71% by weight, greater than or equal to about 0.72% by weight, greater than or equal to about 0.73% by weight, greater than or equal to about 0.74% by weight, or greater than or equal to about 0.75% by weight. When the amount of Al meets the above ranges, the positive electrode active material is structurally stable under high voltage, and the capacity, resistance, or cycle life characteristics of the positive electrode active material can be improved.
[0070] The carbon coating layer is located on the surface of the particles and can improve the particle strength of the second positive electrode active material and prevent its degradation. The carbon coating layer may include graphene with a layered structure of 50 layers or less.
[0071] When large and small particles are mixed, the small particles can degrade relatively quickly, reducing the cycle life of the battery. Because the second positive electrode active material (which includes small particles) includes a carbon coating layer on the surface of the small particles, the degradation of the small particles can be minimized, and the cycle life characteristics of the rechargeable lithium battery can be improved.
[0072] Furthermore, the carbon coating ensures strong adhesion and conductivity to the electrode plate even when small amounts of binder and conductive material are used during the manufacturing of the positive electrode. As the amount of binder or conductive material used in the manufacturing of the positive electrode decreases, the amount of active material in the positive electrode can be increased, enabling rechargeable lithium batteries to exhibit high capacity and high energy density characteristics.
[0073] Meanwhile, techniques have been proposed to coat the surface of particles with amorphous carbon and use them as positive electrode active materials. However, uniform coating is difficult and there are limitations in preventing the degradation of the active material. In the case of positive electrode active materials according to some embodiments of this disclosure, the second positive electrode active material (i.e., small particles) may include a carbon coating layer comprising crystalline carbon provided in a two-dimensional plane. Because the carbon coating layer is provided with a uniform film geometry having a thickness of up to tens of nanometers, the degradation of small particles can be prevented more effectively compared to the case of coating with amorphous carbon, and better cycle life characteristics of rechargeable lithium batteries can be achieved. In addition, the mixing density of the electrode plates can be improved, the electronic conductivity and ionic conductivity of the positive electrode can be improved, the energy density of the rechargeable lithium battery can be increased while reducing the resistance of the positive electrode, and better electrochemical performance of the rechargeable lithium battery can be achieved.
[0074] A layered structure with 50 or fewer layers can be represented as a layered structure with 50 atomic layers or fewer. The carbon coating layer may include graphene with layered structures having 2 to 50 layers, 2 to 48 layers, 5 to 45 layers, 7 to 40 layers, or 10 to 35 layers. The number of layers in the layered structure can be measured by high-resolution transmission electron microscopy (HR-TEM) images of the second positive electrode active material particles.
[0075] The interlayer spacing d of the layered structure 002 The interlayer spacing d of the layered structure can be from about 0.320 nm to about 0.350 nm, for example, from about 0.325 nm to about 0.348 nm, from about 0.328 nm to about 0.345 nm, or from about 0.330 nm to about 0.342 nm. 002 Meeting the above ranges can prevent the deterioration of the second positive electrode active material, improve the particle strength of the second positive electrode active material, and maximize the density of the positive electrode. Interlayer spacing d 002 The interlayer spacing d of the layered structure can be measured using methods known to those skilled in the art. 002 The peaks on the 002 plane can be obtained via X-ray diffraction (XRD) of the carbon-coated layer, and then analyzed. The 002 plane represents the range of 25.0° < 2θ < 27.0°, where 2θ represents the diffraction angle. Standard procedures provided in the XRD apparatus can be used as data processing and analysis procedures to perform noise reduction (i.e., baseline setting) on the XRD measurements. Furthermore, the peak profiles on the 002 plane can be fitted using conventional fitting functions such as Gaussian or Lorentz functions. Additionally, the interlayer spacing d of the layered structure... 002 The interlayer spacing d of plate-shaped carbon materials can be measured. 002 The method is used to represent the interlayer spacing d of the carbon material. 002 This can be measured through XRD analysis of carbon materials. The number of layers and the interlayer spacing (d) in a layered structure can be determined. 002 The thickness of the coating layer was determined as an average of measurements of the cross-section of the core particle at multiple randomly selected locations using HR-TEM. Note that the correlation between these parameters follows the physical properties of the graphene coating layer, where the total thickness of the coating layer is the product of the number of layers and the average interlayer spacing.
[0076] In the carbon coating layer of the second positive electrode active material, the graphene may be derived from a sheet-like carbon material. The carbon material may be represented as a sheet-like carbon material or a 2D carbon material, and may include crystalline carbon. The carbon material may include graphene, graphite, or a combination thereof, and may specifically be, for example, particulate graphite. In some embodiments, the graphene in the carbon coating layer may be derived from particulate graphite. The carbon coating layer has a layered structure exhibiting a dense crystalline structure, including crystalline carbon provided in a two-dimensional plane on the surface of the particles, and may have a thin and uniform thickness. Therefore, degradation of the second positive electrode active material can be reduced, particle strength of the second positive electrode active material can be improved, and the density of the positive electrode can be maximized. Additionally, the electronic conductivity and interfacial resistance of the positive electrode can be improved, lithium-ion insertion and extraction can be more efficient, and ionic conductivity of the positive electrode can be improved because lithium ions diffuse along the layered structure.
[0077] The average size D of carbon materials 50 The average size of the carbon material can be less than or equal to about 2.5 μm, for example, less than or equal to about 1.5 μm, less than or equal to about 1.0 μm, less than 1 μm, or less than or equal to about 0.5 μm; it can be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, or greater than or equal to about 0.08 μm; and it can be about 10 nm to about 1,000 nm, about 30 nm to about 950 nm, or about 50 nm to about 900 nm. When the average size of the carbon material meets the above ranges, a carbon coating layer of uniform thickness can be provided on the surface of the particles, which can reduce the degradation of the second positive electrode active material, improve the particle strength of the second positive electrode active material, and maximize the density of the positive electrode. The average size D of the carbon material... 50 It can be measured by a particle size analyzer and can refer to the size of particles that have a cumulative volume of 50% in the particle size distribution. In addition, particle size can mean the length of the longest axis in the plane direction perpendicular to the thickness direction in a planar geometry.
[0078] The thickness of the carbon material can be less than or equal to about 1.0 μm, for example less than about 1 μm, less than or equal to about 0.9 μm, less than or equal to about 0.7 μm, or less than or equal to about 0.5 μm, and can be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, or greater than or equal to about 0.08 μm. When the thickness of the carbon material meets the above ranges, a carbon coating layer of uniform thickness can be provided on the surface of the particles, which can reduce the degradation of the second positive electrode active material, improve the particle strength of the second positive electrode active material, and maximize the density of the positive electrode. The thickness of the carbon material can be measured by SEM or TEM images of the carbon material particles.
[0079] The carbon material may have a Raman spectral density of about 0.15 to about 0.50, for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G When carbon materials I D / I G When the values meet the above range, a carbon coating layer of uniform thickness can be provided on the surface of the particles, which can reduce the degradation of the second positive electrode active material, improve the particle strength of the second positive electrode active material, and maximize the density of the positive electrode. For example, a Raman spectrometer (e.g., ICRM7000 (Renishaw) etc.) can be used at a laser wavelength of approximately 632 nm and a wavelength of approximately 946 cm⁻¹. -1 The Raman spectra were measured under the condition of the lowest Raman shift. The peak intensity ratios described in this paper are derived from the values at approximately 946 cm⁻¹. -1 The peaks observed were obtained from the Raman shift range starting from the lowest Raman shift. These measurement conditions are standard in the art and the following are within the capabilities of those skilled in the art: adjusting these parameters, such as laser power or exposure time, while maintaining the relative trend of the peak intensity ratio to ensure reproducibility.
[0080] In the second positive electrode active material, based on 100% by weight, a carbon coating layer may be included in an amount from about 0.05% by weight to about 5.0% by weight, for example, from about 0.1% by weight to about 5.0% by weight, from about 0.2% by weight to about 3.0% by weight, from about 0.2% by weight to about 2.5% by weight, from about 0.2% by weight to about 2.0% by weight, from about 0.2% by weight to about 1.0% by weight, or from about 0.2% by weight to about 0.8% by weight. When the amount of carbon coating layer meets the above range, the deterioration of the second positive electrode active material can be reduced, the particle strength of the second positive electrode active material can be improved, and the density of the positive electrode can be maximized. Even if the amount of carbon coating layer is a very small amount, less than about 1% by weight, the carbon coating layer can still be well coated on the surface of the particles, thereby increasing the electrical conductivity of the positive electrode active material, increasing lubricity, and increasing the density of the positive electrode. If the carbon coating layer includes graphene with 50 or fewer layers, the amount of graphene can be described as being the same as the amount of carbon coating layer.
[0081] In the second positive electrode active material, the carbon coating layer can be in the form of a continuous film or an island. The carbon coating layer can be in the form of a film continuously surrounding the surface of the particles, or it can be in the form of a shell surrounding the entire surface of the particles. When a carbon coating layer is provided to completely cover the surface of the particles, the particle strength of the second positive electrode active material can be improved, and the density of the positive electrode can be maximized. Furthermore, the second positive electrode active material can have improved structural stability without increasing resistance or reducing capacity, and the density of the positive electrode including the positive electrode active material can be improved.
[0082] The carbon coating may have a Raman spectral density of about 0.15 to about 0.50, for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G If the carbon coating layer I D / I G If the value meets the above range, the degradation of the second positive electrode active material can be reduced, the particle strength of the second positive electrode active material can be improved, and the density of the positive electrode can be maximized. When the carbon coating layer includes graphene with a layered structure of 50 layers or less, the I of graphene... D / I G It can be combined with the carbon coating layer I D / I G Described in the same way.
[0083] The thickness of the carbon coating layer can be from about 3 nm to about 500 nm, for example, from about 3 nm to about 400 nm, from about 2 nm to about 300 nm, from about 3 nm to about 200 nm, from about 3 nm to about 100 nm, from about 4 nm to about 50 nm, from about 5 nm to about 30 nm, from about 5 nm to about 20 nm, or from about 5 nm to about 15 nm. When the thickness of the carbon coating layer meets the above ranges, the degradation of the second positive electrode active material can be reduced, the particle strength of the second positive electrode active material can be improved, and the density of the positive electrode can be maximized without increasing the resistance or reducing the capacity due to the carbon coating layer. The thickness of the carbon coating layer can be measured by transmission electron microscopy of the cross-section of the positive electrode active material particles cut by FIB (Focused Ion Beam). However, this disclosure is not limited to this, and the thickness of the carbon coating layer can be measured by, for example, SEM, TOF-SIMS, XPS, or EDS analysis, and can be measured by TEM-EDS line profiling.
[0084] The difference between the highest and lowest thicknesses of the carbon coating in a second positive electrode active material can be less than or equal to about 30 nm, for example, less than or equal to about 25 nm, less than or equal to about 20 nm, or less than or equal to about 15 nm and can be greater than or equal to about 0.30 nm, greater than or equal to about 0.33 nm, greater than or equal to about 0.35 nm, or greater than or equal to about 0.40 nm. A difference between the highest and lowest thicknesses of the carbon coating satisfying the above ranges means that a carbon coating of uniform thickness is well provided on the surface of the particles in the form of a film. Therefore, the degradation of the second positive electrode active material can be reduced, the particle strength of the second positive electrode active material can be improved, and the density of the positive electrode can be maximized. The highest and lowest thicknesses of the carbon coating can be measured based on electron microscopy images of the second positive electrode active material. In an electron microscopy image of a cross-section of the second positive electrode active material particles, the thickness of the thickest portion of the cross-section of the carbon coating can be defined as the highest thickness of the carbon coating, and the thickness of the thinnest portion can be defined as the lowest thickness of the carbon coating. The thickness of the carbon coating can be the vertical distance from the outer surface of the particle to the outer surface of the carbon coating. A scanning electron microscope or a transmission electron microscope can be used as the electron microscope.
[0085] Based on a total of 100% by weight of the first and second positive electrode active materials, the second positive electrode active material may be included in an amount of about 5% to about 80% by weight, for example, about 10% to about 70% by weight, about 15% to about 55% by weight, or about 20% to about 40% by weight. When the amount of the second positive electrode active material meets the above range, the energy density of the rechargeable lithium battery can be improved.
[0086] Methods for preparing positive electrode active materials
[0087] A method for preparing a positive electrode active material according to some embodiments may include: preparing a first positive electrode active material, the first positive electrode active material comprising a lithium cobalt-based oxide and having an average particle size D of about 9 μm to about 25 μm. 50 The particles will include lithium cobalt-based oxides and have an average particle size D of about 1 μm to about 9 μm. 50 The particles are dry-mixed with carbon materials to prepare a second positive electrode active material; and the first positive electrode active material and the second positive electrode active material are mixed.
[0088] Preparation of the active material for the first positive electrode
[0089] Preparation includes lithium cobalt-based oxides with an average particle size D of about 9 μm to about 25 μm. 50The first positive electrode active material is a particle. The first positive electrode active material can be described in the same way as the first positive electrode active material described above, and therefore a detailed description of the first positive electrode active material is omitted.
[0090] Preparation of the active material for the second positive electrode
[0091] The material includes lithium cobalt-based oxides and has an average particle size of about 1 μm to about 9 μm. 50 The particles and plate-shaped carbon material are dry-mixed to prepare the second positive electrode active material. Details of the particles and carbon material of the second positive electrode active material are as described above, and therefore a detailed description of the particles and carbon material of the second positive electrode active material is omitted.
[0092] The above processes may include: preparing plate-shaped carbon materials, and dry mixing of particles and carbon materials.
[0093] In the preparation of carbon materials, carbon materials can be produced by forming carbon particles with a sheet-like (scale-like) geometry and an average size D of approximately 3 μm to approximately 25 μm. 50 It is obtained by pulverizing graphite. In some embodiments, it can be obtained by pulverizing graphite having a flake-like geometry and an average size D of about 3 μm to about 25 μm. 50 Graphite was used to prepare materials with an average size D of less than or equal to about 2.5 μm. 50 Particulate graphite (which can be a plate-like carbon material). The average size D of graphite with a flake-like geometry. 50 The graphite can be less than or equal to about 20 μm, less than or equal to about 18 μm, less than or equal to about 15 μm, less than or equal to about 12 μm, or less than or equal to about 10 μm, and can be greater than or equal to about 4 μm, greater than or equal to about 5 μm, or greater than or equal to about 6 μm. The average size of graphite can be measured by scanning electron microscopy images. The average size D of graphite... 50 It can be measured by a particle size analyzer, and means the size of particles that have a cumulative volume of 50% in the particle size distribution. Furthermore, particle size here can mean the length of the longest axis in the plane perpendicular to the thickness direction in a planar geometry.
[0094] Graphite may have a Raman spectroscopy intensity of greater than or equal to about 0.01 and less than about 0.15, for example, about 0.02 to about 0.14, about 0.08 to about 0.14, or about 0.1 to about 0.14 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G .
[0095] Graphite can be pulverized using a grinding process. The grinding process can utilize methods known to those skilled in the art, and can utilize, for example, ball mills, bead mills, spray mills, pin mills, roller mills, mixing mills, colloid mills, or air classifiers (ACMs).
[0096] The pulverization of graphite with a flake-like geometry can be carried out by ball milling, using zirconia beads with a size of about 1 mm to about 25 mm, and at a speed of about 200 rpm to about 5,000 rpm for about 30 minutes to about 4 hours. The size of the zirconia beads used for pulverizing graphite can be about 1.2 mm to about 23 mm, about 1.3 mm to about 21 mm, or about 1.5 mm to about 20 mm. Furthermore, the pulverization of graphite can be carried out at speeds of about 250 rpm to about 4,500 rpm, about 300 rpm to about 4,000 rpm, about 400 rpm to about 3,000 rpm, or about 600 rpm to about 2,000 rpm. The pulverization can be carried out for about 30 minutes to about 3 hours or about 35 minutes to about 3 hours. When the bead size, stirring speed, or stirring time each meets the above ranges, the particle size of the particulate graphite can be controlled to a desired level.
[0097] Dry mixing of particles and carbon materials can be performed using methods known to those skilled in the art, such as dry mixers, homogenizers, or Henschel mixers. Dry mixing of particles and carbon materials reduces manufacturing costs, minimizes degradation of the second positive electrode active material, and improves particle strength and surface lubrication of the second positive electrode active material. "Dry" can mean a state in which there is no intentional contact with solvents such as process solvents, or a state in which solvents are not intentionally included.
[0098] In the process of dry mixing particles and carbon materials, based on a total amount of 100% particles and carbon materials, carbon materials can be mixed in amounts from about 0.05% to about 5.0% by weight, for example, from about 0.2% to about 5.0% by weight, from about 0.2% to about 3.0% by weight, from about 0.2% to about 2.5% by weight, from about 0.2% to about 2.0% by weight, from about 0.2% to about 1.0% by weight, or from about 0.2% to about 0.8% by weight. When the amount of carbon material meets the above range, the deterioration of the second positive electrode active material can be minimized, the particle strength and surface lubrication of the second positive electrode active material can be improved, and the density of the positive electrode can be maximized. Even if the amount of carbon material is a very small amount, less than about 1% by weight, it can well coat the surface of the particles, thereby increasing the electrical conductivity of the positive electrode active material, increasing lubrication, and increasing the density of the positive electrode.
[0099] The process of dry mixing particulate and carbon materials can be carried out by mixing the particulate and carbon materials and applying shear force. A coating layer comprising graphene having a layered structure exhibiting a dense crystalline structure can be provided, while crystalline carbon derived from plate-like carbon materials is located on the surface of the core in a two-dimensional plane. The process can be carried out using a device for applying shear force, and the device may have blades internally, although this disclosure is not limited thereto.
[0100] The process may involve using a mixer, such as a Nobilta mixer, to mix particulate and carbon materials, and the particulate and carbon materials can be mixed in approximately 1,000 s. -1 From approximately 9,000 s -1 The shear rate is mixed with a blade rotation speed of less than or equal to about 20 m / s.
[0101] In the above process, particulate and carbon materials can be processed in approximately 1,500 s. -1 From approximately 8,800 s -1 Approximately 2,000 s -1 From approximately 8,800 s -1 Or approximately 2,500 s -1 From approximately 8,500 s -1 The shear rate is mixed. When the shear rate range meets the above range, a carbon coating layer can be effectively provided on the surface of the particles while preventing damage to the particles.
[0102] The rotational speed of the blades within the device for applying shear force can be less than or equal to about 18 m / s, less than or equal to about 15 m / s, or less than or equal to about 10 m / s and can be greater than or equal to about 3 m / s, greater than or equal to about 4 m / s, or greater than or equal to about 5 m / s. When the rotational speed of the blades falls within the range described above, a coating layer can be effectively provided on the surface of the particles while preventing damage to the particles.
[0103] In the above process, the particles and carbon materials can be mixed at a speed of approximately 500 rpm to approximately 6,000 rpm, for example, at a speed of approximately 600 rpm to approximately 5,500 rpm, approximately 700 rpm to approximately 5,000 rpm, or approximately 800 rpm to approximately 4,000 rpm. When the mixing conditions meet the above range, a coating layer can be effectively provided on the surface of the particles while preventing damage to the particles.
[0104] Mix the first positive electrode active material with the second positive electrode active material.
[0105] The first positive electrode active material and the second positive electrode active material can be mixed. In this process, based on a total of 100% of the first and second positive electrode active materials, the first positive electrode active material can be mixed in an amount of about 20% to about 95% by weight, for example, about 30% to about 90% by weight, about 45% to about 85% by weight, or about 60% to about 80% by weight, and the second positive electrode active material can be mixed in an amount of about 5% to about 80% by weight, for example, about 10% to about 70% by weight, about 15% to about 55% by weight, or about 20% to about 40% by weight. When the amounts of the first and second positive electrode active materials meet the above ranges, the capacity and mixing density of the positive electrode can be improved, and the energy density of the rechargeable lithium battery can be improved.
[0106] positive electrode
[0107] According to some embodiments, the positive electrode may include a current collector and a layer of positive electrode active material on the current collector, wherein the layer of positive electrode active material includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the layer of positive electrode active material may further include other types of positive electrode active materials.
[0108] current collector
[0109] There are no particular limitations on the current collector, as long as it is conductive and does not cause chemical changes in the positive electrode and the rechargeable lithium battery including the positive electrode. The current collector may include thin films of aluminum (Al), stainless steel (SUS), indium (In), magnesium (Mg), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), germanium (Ge), lithium (Li), or combinations thereof, and may specifically include aluminum thin films.
[0110] The geometry of the current collector can take many forms, such as plates, thin sheets, films, sheets, foils, meshes, porous bodies, foams, or nonwoven materials. The current collector can include microscopic irregularities on its surface, which can improve the adhesion of the positive electrode active material.
[0111] The thickness of the current collector can be from about 1 μm to about 20 μm, for example from about 5 μm to about 15 μm or from about 7 μm to about 10 μm.
[0112] The positive electrode active material layer may further include a binder, a conductive material, or a combination thereof.
[0113] adhesive
[0114] The binder can improve the adhesion properties between the positive electrode active material particles and with the current collector. The binder may include one or more of the following: polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers including ethylene oxide (including polymers of ethylene oxide), polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin and nylon, but the binder is not limited to these.
[0115] In the positive electrode active material layer, based on 100% by weight of the total positive electrode active material layer, a binder may be included in an amount from about 0.1% by weight to about 5% by weight, for example, from about 0.5% by weight to about 4% by weight, or from about 1% by weight to about 3% by weight. Based on the total 100% by weight of the positive electrode active material layer, a binder may be included in an amount from about 0.1% by weight to about 1% by weight, for example, less than about 1.0% by weight, or less than or equal to about 0.9% by weight. Because the positive electrode active material layer includes the aforementioned positive electrode active material, even if the positive electrode active material layer does not include a separate binder or includes a very small amount of binder, the positive electrode active material layer can still exhibit excellent electronic conductivity and achieve low resistance and high positive electrode density.
[0116] conductive materials
[0117] The conductive material is included to provide electrode conductivity, and any electrically conductive material may be used as a conductive material unless it causes a chemical change. Conductive materials may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, or carbon nanotubes; metal-based materials containing copper, nickel, aluminum, or silver in the form of metal powders or metal fibers; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0118] In the positive electrode active material layer, based on 100% by weight of the total positive electrode active material layer, conductive material may be included in an amount from about 0.05% by weight to about 5% by weight, for example, from about 0.05% by weight to about 4% by weight, or from about 0.1% by weight to about 3% by weight. Based on the total 100% by weight of the positive electrode active material layer, conductive material may be included in an amount from about 0.05% by weight to about 1% by weight, for example, less than about 1.0% by weight, less than or equal to about 0.8% by weight, less than or equal to about 0.7% by weight, or less than or equal to about 0.5% by weight. Because the positive electrode active material layer includes the aforementioned positive electrode active material, even if the positive electrode active material layer does not include a separate conductive material or includes a very small amount of conductive material, the positive electrode active material layer can still exhibit excellent electronic conductivity and achieve low resistance and high positive electrode density.
[0119] When the density of the positive electrode active material layer meets the above-mentioned range, the energy density of the rechargeable lithium battery can be improved. Because the positive electrode active material included in the positive electrode active material layer has high particle strength and high particle surface lubricity, the compression process can be performed under greater pressure during the manufacturing of the positive electrode. Furthermore, because the surface lubricity of the positive electrode active material is high, the compression efficiency of the positive electrode can be improved through the sliding effect. Additionally, because the compression process can be performed under greater pressure, the number of holes in the electrode plate within the positive electrode active material layer can be reduced, and the density of the positive electrode active material layer can be improved. The density of the positive electrode active material layer means the ratio of the weight of the positive electrode active material layer to the volume of the positive electrode active material layer in the compressed positive electrode. The density of the positive electrode active material layer can be obtained by measuring the cross-sectional area, thickness, and weight of the positive electrode active material layer excluding the positive electrode current collector, calculating the volume by multiplying the cross-sectional area by the thickness, and dividing the weight by the volume.
[0120] The adhesion strength of the positive electrode active material layer to the current collector can be greater than or equal to about 0.5 gf / mm, and the resistivity of the positive electrode active material layer can be less than or equal to about 40 Ω·cm. The adhesion strength of the positive electrode active material layer to the current collector can be greater than or equal to about 1.0 gf / mm, greater than or equal to about 1.5 gf / mm, greater than or equal to about 2.0 gf / mm, or greater than or equal to about 2.5 gf / mm and less than or equal to about 30 gf / mm, less than or equal to about 28 gf / mm, less than or equal to about 25 gf / mm, or less than or equal to about 23 gf / mm. Furthermore, the resistivity of the positive electrode active material layer can be less than or equal to about 35 Ω·cm, less than or equal to about 30 Ω·cm, less than or equal to about 25 Ω·cm, or less than or equal to about 20 Ω·cm and can be greater than or equal to about 0.5 Ω·cm, greater than or equal to about 1.0 Ω·cm, greater than or equal to about 3.0 Ω·cm, greater than or equal to about 5.0 Ω·cm, or greater than or equal to about 5.5 Ω·cm. Because the positive electrode active material layer includes the above-mentioned positive electrode active material, even if the positive electrode active material layer does not include a separate conductive material or includes a very small amount of conductive material, the positive electrode active material layer can exhibit excellent electronic conductivity and achieve low resistance, and even if it includes a very small amount of binder, high electrode plate adhesion strength can be achieved.
[0121] The thickness of the positive electrode active material layer can be from about 40 μm to about 300 μm, for example from about 50 μm to about 200 μm, or from about 80 μm to about 150 μm. When the thickness of the positive electrode active material layer meets the above range, a battery with high capacity and high energy density can be achieved. The thickness of the positive electrode active material layer can be measured by SEM images of the positive electrode cross-section. However, this disclosure is not limited thereto, and the thickness of the positive electrode active material layer can be measured by TEM, TOF-SIMS, XPS, or EDS analysis.
[0122] The porosity of the positive electrode can be less than or equal to about 30%, less than or equal to about 25%, or less than or equal to about 20% and can be greater than or equal to about 1%, greater than or equal to about 5%, or greater than or equal to about 7%. When the porosity of the positive electrode meets the above ranges, the capacity and energy density of the positive electrode can be improved. The porosity of the positive electrode means the ratio of the volume of pores present in the positive electrode to the total volume of the positive electrode, and can be measured, for example, by mercury porosimetry (mercury porosimetry).
[0123] Rechargeable lithium batteries
[0124] A rechargeable lithium battery according to some embodiments may include: a positive electrode comprising a current collector and a positive electrode active material layer on the current collector, wherein the positive electrode active material layer comprises the aforementioned positive electrode active material; a negative electrode; and an electrolyte. The rechargeable lithium battery may be a lithium-ion battery using a liquid electrolyte, or an all-solid-state rechargeable battery or a semi-solid-state rechargeable battery using a solid electrolyte.
[0125] Depending on the geometry of the rechargeable lithium battery, rechargeable lithium batteries can be classified as cylindrical, prismatic, pouch-shaped, or coin-shaped.
[0126] Figures 1 to 4 This is a schematic diagram illustrating a rechargeable lithium battery according to some embodiments of the present disclosure. Specifically, Figure 1 Displays a cylindrical battery. Figure 2 Displays a prismatic battery, and Figure 3 and 4 Each displays a battery with a pouch-like geometry.
[0127] The rechargeable lithium battery 100 includes an electrode assembly 40 and a housing 50. The electrode assembly 40 has a separator 30 between a positive electrode 10 and a negative electrode 20, and the electrode assembly 40 is housed within the housing 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution (not shown). The rechargeable lithium battery 100 may include a seal 60 for sealing the housing 50, such as... Figure 1 As shown. Additionally, in Figure 2In this context, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12, a negative electrode lead connector 21, and a negative electrode terminal 22. For example... Figure 3 and 4 As shown, the rechargeable lithium battery 100 includes electrode terminals 70, and specifically includes a positive electrode terminal 71 and a negative electrode terminal 72, which serve as electrical paths for leading current supplied in the electrode assembly 40 to the outside.
[0128] According to some embodiments, rechargeable lithium batteries may be rechargeable at high voltage or suitable for driving at high voltage. The charging voltage of the rechargeable lithium battery may be greater than or equal to about 4.45 V, about 4.45 V to about 4.7 V, about 4.45 V to about 4.6 V, or about 4.45 V to about 4.55 V. By applying the positive electrode active material according to some embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even when charging at high voltage and achieve high capacity and long cycle life characteristics.
[0129] negative electrode
[0130] The negative electrode may include a current collector and a layer of negative electrode active material on the current collector. The negative electrode active material layer may include a negative electrode active material and may further include a binder, a conductive material, or a combination thereof.
[0131] Negative electrode active material
[0132] The negative electrode active material may include materials capable of reversibly inserting / deintercalating lithium ions, lithium metal, lithium metal alloys, materials capable of doping and dedoping lithium, or transition metal oxides.
[0133] Materials capable of reversibly inserting / deintercalating lithium ions may include carbon-based negative electrode active materials, such as crystalline carbon, amorphous carbon, or combinations thereof. Crystalline carbon may be irregular, flake-like, spherical, or fibrous natural graphite and / or artificial graphite. Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization products, or calcined coke.
[0134] As an alloy of lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn can be used.
[0135] Materials capable of doping and dedoping lithium can be Si-based or Sn-based negative electrode active materials. Si-based negative electrode active materials can be silicon, silicon-carbon composites, or SiO₂. x(0<x≤2), a Si-Q alloy (where Q is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element [excluding Si], a Group 15 element, a Group 16 element, a transition metal, a rare earth element, or a combination thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof), or a combination thereof. The Sn-based negative electrode active material may be Sn, SnO₂, a Sn-based alloy, or a combination thereof.
[0136] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle diameter D of the silicon-carbon composite particles 50 may be, for example, from about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surfaces of the silicon particles. The silicon-carbon composite may include secondary particles (core) in which silicon primary particles are aggregated, and an amorphous carbon coating layer (shell) on the surfaces of the secondary particles. Amorphous carbon may also be present between the silicon primary particles. In some embodiments, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be present dispersed in an amorphous carbon matrix.
[0137] The silicon-carbon composite may further include crystalline carbon. The silicon-carbon composite may include: a core comprising crystalline carbon and silicon particles, and an amorphous carbon coating layer on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft carbon or hard carbon, a mesophase pitch carbonization product, and / or calcined coke.
[0138] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be from about 10 wt% to about 50 wt%, and the amount of amorphous carbon may be from about 50 wt% to about 90 wt%. In addition, when the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be from about 10 wt% to about 50 wt%, the amount of crystalline carbon may be from about 10 wt% to about 70 wt%, and the amount of amorphous carbon may be from about 20 wt% to about 40 wt%.
[0139] In addition, the thickness of the amorphous carbon coating layer may be from about 5 nm to about 100 nm. The average particle diameter D of the silicon particles (primary particles) 50 may be from about 10 nm to about 1 μm or from about 10 nm to about 200 nm. The silicon particles may be present as elemental silicon, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon may be represented by SiO x(0<x≤2). The atomic ratio of Si:O indicating the oxidation degree may be from about 99:1 to about 33:67.
[0140] The Si-based negative electrode active material or Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material is used in combination with the carbon-based negative electrode active material, the weight ratio of the Si-based negative electrode active material or Sn-based negative electrode active material to the carbon-based negative electrode active material may be from about 1:99 to about 90:10.
[0141] Based on 100% by weight of the total negative electrode active material layer, the negative electrode active material may be included in an amount of about 80 wt% to about 99 wt%, for example, about 85 wt% to about 99 wt% or about 90 wt% to about 99 wt%.
[0142] adhesive
[0143] The binder serves to adhere the negative electrode active material particles to each other, and also serves to adhere the negative electrode active material to the current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.
[0144] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or a combination thereof.
[0145] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or a combination thereof.
[0146] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. The alkali metal may be Na, K or Li.
[0147] The dry binder may be a polymeric material capable of forming fibers, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.
[0148] Based on 100% by weight of the total negative electrode active material layer, the binder may be included in an amount of about 0.5% by weight to about 5% by weight, for example, about 0.5% by weight to about 4% by weight or about 1% by weight to about 3% by weight.
[0149] conductive materials
[0150] This includes conductive materials to provide electrode conductivity, and any electrically conductive material can be used as a conductive material unless it causes a chemical change. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers and / or carbon nanotubes; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum and / or silver; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0151] Based on 100% by weight of the total negative electrode active material layer, conductive material may be included in an amount of about 0.5% by weight to about 5% by weight, for example, about 0.5% by weight to about 4% by weight or about 1% by weight to about 3% by weight.
[0152] current collector
[0153] There are no particular restrictions on the negative electrode current collector, as long as it does not cause chemical changes in the negative electrode and the rechargeable lithium battery including the negative electrode. The negative electrode current collector can be copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0154] The negative electrode current collector can be one or more of various geometries, such as a plate, thin film, membrane, sheet, foil, mesh, porous body, foam, or nonwoven material. The negative electrode current collector may include microscopic irregularities on its surface, which can improve the adhesion strength to the negative electrode active material.
[0155] The thickness of the negative electrode current collector can be from about 1 μm to about 20 μm, for example from about 5 μm to about 15 μm or from about 7 μm to about 10 μm.
[0156] electrolytes
[0157] The electrolyte used in rechargeable lithium batteries may be an electrolyte solution, which may include non-aqueous organic solvents and lithium salts.
[0158] Non-aqueous organic solvents can be used as media for transporting ions that participate in the electrochemical reactions of a battery. Non-aqueous organic solvents can be carbonate (carbonate-based) solvents, ester (ester-based) solvents, ether (ether-based) solvents, ketone (ketone-based) solvents, alcohol (alcohol-based) solvents, aprotic solvents, or combinations thereof.
[0159] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and / or butyl carbonate (BC).
[0160] Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valproic acid lactone, and / or caprolactone.
[0161] Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran and / or tetrahydrofuran.
[0162] Ketone solvents may include cyclohexanone. Alcohol solvents may include ethanol and / or isopropanol, and aprotic solvents may include nitriles such as R-CN (where R is a C2 to C20 straight-chain, branched, or cyclic hydrocarbon group, and may include double bonds, aromatic rings, and / or ether groups); amides such as dimethylformamide; dioxolane such as 1,3-dioxolane and / or 1,4-dioxolane; and / or sulfolane.
[0163] Non-aqueous organic solvents can be used alone or in mixtures of two or more types, and when two or more types are used in mixtures, the mixing ratio can be appropriately adjusted according to the desired battery performance, as is widely known to those skilled in the art.
[0164] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used, and cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.
[0165] Non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. Carbonate solvents and aromatic hydrocarbon organic solvents may be mixed and used in a volume ratio of about 1:1 to about 30:1.
[0166] The electrolyte solution may further include vinylene carbonate, vinylene carbonate, or ethylene carbonate compounds to improve the cycle life of rechargeable lithium batteries.
[0167] Examples of ethylene carbonate compounds may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0168] Lithium salts dissolved in organic solvents can supply lithium ions in batteries, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts may include one or more selected from the following: LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).
[0169] The concentration of lithium salt can range from about 0.1 M to about 2.0 M. When the concentration of lithium salt is within this range, the electrolyte solution has suitable ionic conductivity and viscosity. Therefore, excellent performance of rechargeable lithium batteries can be achieved, and lithium ions can move efficiently.
[0170] diaphragm
[0171] Depending on the type of rechargeable lithium battery, the rechargeable lithium battery may further include a separator between the positive and negative electrodes. The separator may include a multilayer membrane of polyethylene, polypropylene, polyvinylidene fluoride, or two or more layers thereof, and may include mixed multilayer membranes such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, and / or a polypropylene / polyethylene / polypropylene three-layer separator.
[0172] The diaphragm may include a porous substrate and a coating on one or both surfaces of the porous substrate, comprising organic materials, inorganic materials, or combinations thereof.
[0173] The porous substrate may be a polymer membrane provided by any of the following polymers: polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyacetal; polyamide; polyimide; polycarbonate; polyetherketone; polyaryletherketone; polyetherimide; polyamideimide; polybenzimidazole; polyethersulfone; polyphenylene ether; cyclic olefin copolymers; polyphenylene sulfide; polyethylene naphthalate; and Teflon (polytetrafluoroethylene); or copolymers or mixtures of two or more thereof. The porous substrate may include glass fiber, or may include a composite membrane of polymer and glass fiber.
[0174] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0175] Organic materials may include (meth)acrylic acid copolymers, which include a first structural unit and a second structural unit derived from (meth)acrylamide, the second structural unit including at least one structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acryloylaminosulfonic acid or a salt thereof.
[0176] Inorganic materials may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, Ga2O3, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but are not limited to these. The average particle size D of the inorganic particles... 50 It can be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm, or from about 100 nm to about 700 nm. The average particle size D of the inorganic particles. 50 The particle size distribution can be obtained by randomly selecting about 20 particles from the scanning electron microscope image of inorganic particles, measuring their particle size (diameter, major axis, or major axis length), and then taking the size of the particles with a cumulative volume of 50% from the particle size distribution as the average particle size.
[0177] Organic and inorganic materials can be mixed in a single coating, or coatings comprising organic materials and coatings comprising inorganic materials can be stacked. The thickness of the coating can be from about 0.5 μm to about 20 μm, for example from about 1 μm to about 10 μm, or from about 1 μm to about 5 μm.
[0178] Rechargeable lithium batteries according to some embodiments can be used in automobiles, mobile phones or various types of electronic devices, but rechargeable lithium batteries are not limited to these.
[0179] The following describes embodiments and comparative examples of the present invention. These embodiments are for illustrative purposes only, and the present invention is not limited to these embodiments.
[0180] Example 1
[0181] (1) Preparation of positive electrode active material
[0182] (a) Preparation of the active material for the first positive electrode
[0183] Prepare a LiCoO2 (LCO) composition with an average particle size D of 17 μm.50 The particles are used as the active material of the first positive electrode.
[0184] (b) Preparation of the active material for the second positive electrode
[0185] Graphite with a flake-like (scaly) geometry (DJrGO-SF (Dongjin Semichem), average particle size D) 50 The graphite was mixed with ZrO2 beads having a particle size of 2 mm (3 μm), the ZrO2 beads being 10 times the weight of the graphite. Subsequently, the graphite and beads were milled together at 1,000 rpm for 1 hour to prepare a D-type graphite with an average particle size of 100 nm. 50 Graphite microparticles.
[0186] In preparing a composition with LiCoO2 (LCO) and an average particle size D of 5 μm 50 After the particles were removed, 99.8% by weight of the particles and 0.2% by weight of the graphite microparticles were placed in a dry mixer. The shear rate was then adjusted to 5,000 s⁻¹. -1 Then, after setting the rotation speed of the blades in the mixer to 10 m / s, the particles and graphite microparticles were mixed for 10 minutes to prepare the second positive electrode active material.
[0187] (c) Preparation of positive electrode active material
[0188] The first positive electrode active material and the second positive electrode active material are mixed at a weight ratio of 70:30 to prepare the positive electrode active material.
[0189] (2) Manufacturing of the positive electrode
[0190] A positive electrode active material slurry was prepared by dispersing 99.1% by weight of the positive electrode active material prepared in part (1) of Example 1, 0.2% by weight of carbon nanotubes (used as a conductive material), and 0.7% by weight of polyvinylidene fluoride (used as a binder) in an N-methylpyrrolidone (NMP) solvent. The positive electrode active material slurry was coated onto a 12 μm thick aluminum substrate (current collector) and dried to form a positive electrode active material layer, and then compressed to manufacture a positive electrode.
[0191] (3) Manufacturing of rechargeable lithium battery cells
[0192] The positive electrode and lithium metal counter electrode manufactured in part (2) of Example 1 are used, and a separator having a polyethylene-polypropylene multilayer structure is placed between the positive electrode and the lithium metal counter electrode. An electrolyte solution (prepared by adding 1.3 M LiPF6 lithium salt to a solvent comprising ethylene carbonate, propylene carbonate, and propyl propionate mixed in a volume ratio of 10:15:75) is injected into the electrode assembly of the positive electrode, separator, and lithium metal counter electrode to manufacture a rechargeable lithium battery cell.
[0193] Example 2
[0194] The positive electrode active material, the positive electrode, and the rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 1, except that 99.5% by weight of particles and 0.5% by weight of graphite microparticles were mixed in “(1) Preparation of positive electrode active material” in Example 1.
[0195] Example 3
[0196] The positive electrode active material, the positive electrode, and the rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that 99.0% by weight of particles and 1.0% by weight of graphite microparticles were mixed in “(1) Preparation of positive electrode active material” in Example 1.
[0197] Example 4
[0198] The positive electrode active material, the positive electrode, and the rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that 98.0% by weight of particles and 2.0% by weight of graphite microparticles were mixed in “(1) Preparation of positive electrode active material” in Example 1.
[0199] Comparative Example 1
[0200] (1) Preparation of positive electrode active material
[0201] (a) Preparation of the active material for the first positive electrode
[0202] Graphite with a flake-like geometry (DJrGO-SF (Dongjin Semichem), average particle size D) 50 Graphite (3 μm) was mixed with ZrO2 beads having a particle size of 2 mm, the ZrO2 beads being 10 times the weight of graphite. Subsequently, the graphite and beads were milled together at 1,000 rpm for 1 hour to prepare a D-type graphite with an average particle size of 100 nm. 50 Graphite microparticles.
[0203] In preparing a composition with LiCoO2 (LCO) and an average particle size D of 17 μm 50 After the particles were removed, 99.8% by weight of the particles and 0.2% by weight of the graphite microparticles were placed in a dry mixer. The shear rate was set to 5,000 s⁻¹. -1 Then, after setting the rotation speed of the blades in the mixer to 10 m / s, the particles and graphite microparticles were mixed for 10 minutes to prepare the first positive electrode active material.
[0204] (b) Preparation of the active material for the second positive electrode
[0205] In the preparation of LiCoO2 (LCO) with an average particle size of 5 μm, 50 After the particles were removed, 99.8% by weight of the particles and 0.2% by weight of the graphite microparticles used in Comparative Example 1 (“(a) Preparation of the first positive electrode active material”) were placed in a dry mixer. The shear rate was set to 5,000 s⁻¹. -1 Then, after setting the rotation speed of the blades in the mixer to 10 m / s, the particles and graphite microparticles were mixed for 10 minutes to obtain the second positive electrode active material.
[0206] (c) Preparation of positive electrode active material
[0207] The first positive electrode active material and the second positive electrode active material are mixed at a weight ratio of 70:30 to prepare the positive electrode active material.
[0208] (2) Manufacturing of positive electrode and rechargeable lithium battery cell
[0209] The positive electrode and rechargeable lithium battery cell were manufactured using the positive electrode active material of Comparative Example 1 in substantially the same manner as in Example 1.
[0210] Comparative Example 2
[0211] (1) Preparation of positive electrode active material
[0212] (a) Preparation of the active material for the first positive electrode
[0213] Graphite with a flake-like geometry (DJrGO-SF (Dongjin Semichem), average particle size D) 50 The graphite was mixed with ZrO2 beads having a particle size of 2 mm (3 μm), the ZrO2 beads being 10 times the weight of the graphite. Subsequently, the graphite and beads were milled together at 1,000 rpm for 1 hour to prepare a D-type graphite with an average particle size of 100 nm. 50 Graphite microparticles.
[0214] In preparing a composition with LiCoO2 (LCO) and an average particle size D of 17 μm 50 After the particles were removed, 99.8% by weight of the particles and 0.2% by weight of the graphite microparticles were placed in a dry mixer. The shear rate was set to 5,000 s⁻¹. -1 Then, after setting the rotation speed of the blades in the mixer to 10 m / s, the particles and graphite microparticles were mixed for 10 minutes to obtain the first positive electrode active material.
[0215] (b) Preparation of the active material for the second positive electrode
[0216] Prepare a LiCoO2 (LCO) composition with an average particle size D of 5 μm. 50 The particles are used as the active material for the second positive electrode.
[0217] (c) Preparation of positive electrode active material
[0218] The first positive electrode active material and the second positive electrode active material are mixed at a weight ratio of 70:30 to prepare the positive electrode active material.
[0219] (2) Manufacturing of positive electrode and rechargeable lithium battery cell
[0220] The positive electrode and rechargeable lithium battery cell were manufactured using the positive electrode active material of Comparative Example 2 in substantially the same manner as in Example 1.
[0221] Comparative Example 3
[0222] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 1, except that in “(b) Preparation of the second positive electrode active material” of Example 1, carbon black (product name: Super P, manufacturer: TIMCAL Graphite & Carbon) was used instead of graphite microparticles to prepare the second positive electrode active material.
[0223] Comparative Example 4
[0224] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 1, except that in “(b) Preparation of the second positive electrode active material” of Example 1, carbon nanotubes (product name: Flotube 6807, manufacturer: Canano) were mixed with the particles instead of graphite microparticles to prepare the second positive electrode active material.
[0225] Evaluation Example 1: Electron Microscope Image Analysis
[0226] Figure 5Scanning electron microscope images showing the surface of the second positive electrode active material according to some embodiments of the present disclosure, and Figure 6 Transmission electron microscope images showing a cross-section of the second positive electrode active material according to some embodiments of this disclosure. In particular, Figure 5 and 6 The second positive electrode active material of Example 1 is shown.
[0227] It was confirmed that the second positive electrode active material of Example 1 has a carbon coating layer with a layered structure on the surface of the particles. In addition, the coating layer has a very thin and uniform thickness and continuously surrounds the surface of the core particles.
[0228] Furthermore, the cross-section of the second positive electrode active material in Example 1 was prepared using focused ion beam (FIB) and observed by transmission electron microscopy (TEM). The results confirmed the formation of a coating layer comprising a layered graphene structure having two or more layers on the second positive electrode active material. Additionally, the thickness of the coating layer was approximately 1.6 nm to approximately 5.5 nm.
[0229] Evaluation Example 2: Analysis of the physical properties of the positive electrode active material
[0230] The particle strength of the positive electrode active materials of the analyzed examples and comparative examples is shown in Table 1 below. The specific evaluation method for analyzing the positive electrode active materials is as follows: After placing the active material particles on a plate, the compression force was increased by using a micro compression tester (product name: MCT-W500, manufacturer: Shimadzu Corp.), the force when the particles were broken was measured, and the force of a total of 20 particles was measured and averaged to obtain the particle strength.
[0231] Evaluation Example 3: Analysis of the physical properties of the positive electrode
[0232] The density of the positive electrode active material layer of the positive electrode in the analytical examples and comparative examples is shown in Table 1. The specific evaluation method for the positive electrode is as follows: the cross-sectional area, thickness, and weight of the positive electrode active material layer, excluding the positive electrode current collector, are measured; then, the cross-sectional area is multiplied by the thickness to obtain the volume; and the weight is divided by the volume to calculate the density of each positive electrode active material layer.
[0233] Evaluation Example 4: Performance Analysis of a Rechargeable Lithium-ion Battery Cell
[0234] The initial discharge capacity, capacity retention (cycle life characteristics), and high-temperature storage characteristics of the rechargeable lithium-ion battery cells of the Examples and Comparative Examples are analyzed, and the results are shown in Table 1. The specific evaluation methods for the rechargeable lithium-ion battery cells are as follows, as described in sections (1) to (3) below.
[0235] (1) Initial discharge capacity
[0236] At 25°C, rechargeable lithium-ion battery cells were charged under constant current (0.2 C) and constant voltage (4.25 V; 0.05 C cutoff), paused for 10 minutes, and then discharged to 3.0 V under constant current (0.2 C) for the initial charge and discharge steps. Here, the initial discharge capacity of the battery cells was measured.
[0237] (2) Capacity retention
[0238] After the initial charge and discharge, the individual cells were repeatedly charged and discharged 50 times at 0.5 C / 0.5 C at 25°C to measure the discharge capacity at the 50th cycle. The percentage of the discharge capacity at the 50th cycle to the discharge capacity at the 1st cycle was calculated and then displayed as the capacity retention rate (i.e., cycle life characteristic).
[0239] (3) Storage characteristics at high temperatures
[0240] The rechargeable lithium-ion battery cells were charged at 4 A and 4.2 V at room temperature (25°C), cut off at 100 mA, and then paused for 30 minutes. Subsequently, the battery cells were discharged at 10 A for 10 seconds, 1 A for 10 seconds, and 10 A for 4 seconds, respectively. The current and voltage were then measured at 18 seconds and 23 seconds to calculate DC-IR (the difference between the resistance at 18 seconds and the resistance at 23 seconds) according to ΔR=ΔV / ΔI.
[0241] The rechargeable lithium battery cells were left to stand at 0.2 C and 4.2 V charging conditions and at 60°C for 50 days to measure DC-IR. The percentage of DC-IR after standing to the initial DC-IR was then calculated, which is shown as the rate of increase in resistance (i.e., storage characteristics at high temperatures).
[0242] Table 1:
[0243]
[0244] Referring to Table 1, Examples 1 to 4 exhibit a low resistance increase rate of 55% to 65% and excellent storage characteristics at high temperatures. Furthermore, Examples 1 to 4 exhibit a capacity retention rate of 90% to 92% and excellent cycle life characteristics. Additionally, Examples 1 to 4 were confirmed to exhibit high particle strength, high density of the positive electrode active material layer, and high initial discharge capacity.
[0245] On the other hand, compared with Examples 1 to 4, Comparative Example 1, which includes a carbon coating layer on the surface of the first positive electrode active material and the second positive electrode active material, exhibited significantly deteriorated storage characteristics and cycle life characteristics at high temperatures. Furthermore, it was confirmed that, compared with Examples 1 to 4, Comparative Example 1 exhibited lower particle strength, lower density of the positive electrode active material layer, and lower initial discharge capacity.
[0246] Furthermore, compared to Examples 1 to 4, Comparative Example 2, which did not include a carbon coating layer on the surface of the second positive electrode active material, exhibited deteriorated storage characteristics at high temperatures and deteriorated cycle life characteristics. Additionally, it was confirmed that, compared to Examples 1 to 4, Comparative Example 2 exhibited lower particle strength, lower density of the positive electrode active material layer, and lower initial discharge capacity.
[0247] Furthermore, compared to Examples 1 to 4, Comparative Examples 3 and 4, whose carbon coating layers were derived from Super P or carbon nanotubes respectively, exhibited significantly degraded storage characteristics at high temperatures and significantly degraded cycle life characteristics. Additionally, it was confirmed that, compared to Examples 1 to 4, Comparative Examples 3 and 4 exhibited lower particle strength, lower density of the positive electrode active material layer, and lower initial discharge capacity.
[0248] While the invention has been described in conjunction with some practical embodiments, this disclosure is not limited to the embodiments described above. This disclosure is intended to cover various modifications and equivalent arrangements of the above embodiments.
[0249] <Description of reference numerals in the attached figures>
[0250] 100: Rechargeable lithium battery; 10: Positive electrode
[0251] 11: Positive electrode lead connector 12: Positive electrode terminal
[0252] 20: Negative electrode 21: Negative electrode lead connector
[0253] 22: Negative electrode terminal; 30: Diaphragm
[0254] 40: Electrode assembly; 50: Housing
[0255] 60: Seal 70: Electrode terminal
[0256] 71: Positive electrode connector; 72: Negative electrode connector
Claims
1. Positive electrode active material, including: A first positive electrode active material, comprising particles containing lithium cobalt-based oxide, wherein the particles of the first positive electrode active material have an average particle size D of 9 μm to 25 μm. 50 ;and The second positive electrode active material comprises particles containing lithium cobalt-based oxide and a layered carbon coating layer on the surface of the particles. The particles of the second positive electrode active material have an average particle size D of 1 μm to 9 μm. 50 .
2. The positive electrode active material according to claim 1, wherein the second positive electrode active material comprises the carbon coating layer in an amount of 0.05% to 5.0% by weight, based on 100% by weight of the second positive electrode active material.
3. The positive electrode active material according to claim 1, wherein the carbon coating layer of the second positive electrode active material comprises graphene having a layered structure comprising 2 to 50 layers.
4. The positive electrode active material according to claim 3, wherein the graphene in the carbon coating layer is derived from plate-shaped carbon material.
5. The positive electrode active material according to claim 4, wherein the carbon material comprises graphene, graphite, or a combination thereof.
6. The positive electrode active material according to claim 4, wherein the average size D of the carbon material is... 50 It is less than or equal to 2.5 μm.
7. The positive electrode active material according to claim 4, wherein the average size D of the carbon material is... 50 The range is from 50 nm to 900 nm.
8. The positive electrode active material according to claim 4, wherein the thickness of the carbon material is less than or equal to 1.0 μm.
9. The positive electrode active material according to claim 1, wherein the carbon coating layer is in the form of a continuous film or islands.
10. The positive electrode active material according to claim 1, wherein the carbon coating layer has a density of 0.15 to 0.50 as indicated by its Raman spectrum at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I represents D / I G .
11. The positive electrode active material according to claim 1, wherein the first positive electrode active material comprises less than or equal to 0.01% by weight of carbon material on the surface of each particle of the first positive electrode active material.
12. The positive electrode active material according to claim 1, wherein the lithium cobalt-based oxide of the first positive electrode active material and the lithium cobalt-based oxide of the second positive electrode active material are the same as or different from each other, and each is independently represented by: Li a1 Co x1 M 1 y1 O 2-b1 X b1 , Where 0.9≤a1≤1.8, 0.7≤x1≤1, 0≤y1≤0.3, 0.9≤x1+y1≤1.1, and 0≤b1≤0.1, Where M 1 It is one or more elements of Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, and Where X is one or more elements of F, P and S.
13. The positive electrode active material according to claim 1, wherein the lithium cobalt-based oxide of the first positive electrode active material and the lithium cobalt-based oxide of the second positive electrode active material each further contain aluminum, and The amount of aluminum in the second positive electrode active material based on 100% by weight of the total metals other than lithium in the second positive electrode active material is greater than the amount of aluminum in the first positive electrode active material based on 100% by weight of the total metals other than lithium in the first positive electrode active material.
14. The positive electrode active material according to claim 1, wherein, based on a total of 100% by weight of the first positive electrode active material and the second positive electrode active material, the positive electrode active material comprises the first positive electrode active material in an amount of 20% by weight to 95% by weight, and The first positive electrode active material and the second positive electrode active material comprise a total of 100% by weight, wherein the positive electrode active material includes the second positive electrode active material in an amount of 5% to 80% by weight.
15. A method for preparing the positive electrode active material according to any one of claims 1 to 14, the method comprising: Prepare a first positive electrode active material, the first positive electrode active material comprising particles containing lithium cobalt-based oxide, the particles of the first positive electrode active material having an average particle size D of 9 μm to 25 μm. 50 ; The second positive electrode active material is prepared by dry mixing particles of the second positive electrode active material with plate-shaped carbon material. The particles of the second positive electrode active material include lithium cobalt-based oxide and have an average particle size D of 1 μm to 9 μm. 50 ;as well as The first positive electrode active material and the second positive electrode active material are mixed.
16. The method of claim 15, further comprising preparing the carbon material such that the carbon material has an average size D less than or equal to 2.5 μm. 50 .
17. The method of claim 15, wherein preparing the second positive electrode active material comprises: The particles of the second positive electrode active material and the carbon material are mixed using a mixer; and At 1,000 s -1 Up to 9,000 s -1 The particles of the second positive electrode active material and the carbon material are mixed at a shear rate of less than or equal to 20 m / s and using a blade rotation speed of less than or equal to 20 m / s.
18. The method of claim 15, wherein preparing the second positive electrode active material comprises mixing the particles of the second positive electrode active material with an amount ranging from 0.05% to 5.0% by weight of the carbon material, based on a total of 100% by weight of the particles of the second positive electrode active material and the carbon material.
19. A rechargeable lithium battery, comprising: Positive electrode; negative electrode; as well as Electrolytes, The positive electrode includes: Current collector, and The positive electrode active material layer on the current collector, The positive electrode active material layer thereunder comprises the positive electrode active material according to any one of claims 1 to 14.